The Examined Life. A Tribute to Edmund Pellegrino - Solomon, Mildred Z. (The Hastings Center report, 2013)
Edmund Pellegrino was a huge figure who leaves a huge legacy. Since his death on June 13, 2013, much has been written to honor his prodigious accomplishments in scholarship, public policy, and institution-building and to express gratitude for his kindness, humility, and sense of humor. I want to honor his commitment to living a life in which ideas mattered. For him, ideas were not just the stuff by which to build an academic career or rocks to hurl at opposing scholars and policy-makers.